1986
DOI: 10.1063/1.336938
|View full text |Cite
|
Sign up to set email alerts
|

Photoluminescence killer center in AlGaAs grown by molecular-beam epitaxy

Abstract: Origin of a nonradiative center in AlGaAs grown by molecular-beam epitaxy was investigated by secondary ion mass spectroscopy and deep-level transient spectroscopy, from the change of photoluminescence intensity with anneal treatment, and from its comparison with GaAs. Aluminum-oxygen complex is a most probable defect which acts as a nonradiative center in AlGaAs, and the oxygen would evaporate as Al2O from the surface, which would be a reason why the photoluminescence intensity increases under higher substrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
20
0

Year Published

1989
1989
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(23 citation statements)
references
References 21 publications
3
20
0
Order By: Relevance
“…Aluminum alloying in both MOCVD and MBE Al x Ga 1Ϫx As is known to bring residual oxygen impurities into the host material in high concentrations. 13,14 Oxygen codoping is known to enhance the Er 3ϩ emission in GaAs and Al x Ga 1Ϫx As. 8,15 It should be reiterated that the GaAs:Er sample used in this work also contains oxygen, but the amount of oxygen will obviously remain constant in the pressure experiments.…”
Section: B Effects On the Low Temperature Intensitymentioning
confidence: 99%
“…Aluminum alloying in both MOCVD and MBE Al x Ga 1Ϫx As is known to bring residual oxygen impurities into the host material in high concentrations. 13,14 Oxygen codoping is known to enhance the Er 3ϩ emission in GaAs and Al x Ga 1Ϫx As. 8,15 It should be reiterated that the GaAs:Er sample used in this work also contains oxygen, but the amount of oxygen will obviously remain constant in the pressure experiments.…”
Section: B Effects On the Low Temperature Intensitymentioning
confidence: 99%
“…The energies of states Α and N were determined at low emission rates, when they were well separated from the trap C. The dominant trap C is clearly related to the well-known DX (Si). The trap D observed at a low concentration has been identified as E6 which is related to a complex associated with Ga vacancy and an oxygen atom [4] or an Al-O complex [5]. The traps Α and B well fit to unidentifled levels labelled E1 and E2 that were often observed in AlGaAs grown by MBE [6].…”
mentioning
confidence: 99%
“…As evidenced by the spectra, a deep trap with the thermal activation energy of 0.78 eV below the conduction band was commonly present in the structures studied. On the basis of its thermal characteristic, the trap was found to be very similar to the trap at ΕC -0.76 eV observed in Al x Ga1-x As and identified as the main PL killer related to oxygen or the aluminium-oxygen comp lex [5]. We have found that the trap shows an accumulation at heterointerface as determined from its concentration proflle [6].…”
mentioning
confidence: 62%